Abscopal Effect and Drug-Induced Xenogenization: A Strategic Alliance in Cancer Treatment? - Franzese, Ornella; Torino, Francesco; Giannetti, Elisa; Cioccoloni, Giorgia; Aquino, Angelo; Faraoni, Isabella; Fuggetta, Maria Pia; De Vecchis, Liana; Giuliani, Anna; Kaina, Bernd; Bonmassar, Enzo (International journal of molecular sciences, 2021)
The current state of cancer treatment is still far from being satisfactory considering the strong impairment of patients’ quality of life and the high lethality of malignant diseases. Therefore, it is critical for innovative approaches to be tested in the near future. In view of the crucial role that is played by tumor immunity, the present review provides essential information on the immune-mediated effects potentially generated by the interplay between ionizing radiation and cytotoxic antitumor agents when interacting with target malignant cells. Therefore, the radiation-dependent abscopal effect (i.e., a biological effect of ionizing radiation that occurs outside the irradiated field), the influence of cancer chemotherapy on the antigenic pattern of target neoplastic cells, and the immunogenic cell death (ICD) caused by anticancer agents are the main topics of this presentation. It is widely accepted that tumor immunity plays a fundamental role in generating an abscopal effect and that anticancer drugs can profoundly influence not only the host immune responses, but also the immunogenic pattern of malignant cells. Remarkably, several anticancer drugs impact both the abscopal effect and ICD. In addition, certain classes of anticancer agents are able to amplify already expressed tumor-associated antigens (TAA). More importantly, other drugs, especially triazenes, induce the appearance of new tumor neoantigens (TNA), a phenomenon that we termed drug-induced xenogenization (DIX). The adoption of the abscopal effect is proposed as a potential therapeutic modality when properly applied concomitantly with drug-induced increase in tumor cell immunogenicity and ICD. Although little to no preclinical or clinical studies are presently available on this subject, we discuss this issue in terms of potential mechanisms and therapeutic benefits. Upcoming investigations are aimed at evaluating how chemical anticancer drugs, radiation, and immunotherapies are interacting and cooperate in evoking the abscopal effect, tumor xenogenization and ICD, paving the way for new and possibly successful approaches in cancer therapy.